The Rizal Provincial Library an evaluation of its library collection and services - Alberto, Lizbeth L. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1996)
This study is undertaken to evaluate the library collection and services of the Rizal Provincial Library. The following are the objectives of this study: 1) to find out the holdings of the library; 2) to know the extent of the collection being used by its clientele; 3) to determine whether the library collection is able to support the information, education, social, and recreation needs of its clientele; 4) to know the different services offered by the Rizal Provincial Library to its clientele; 5) to determine whether the library complies with the Minimum Standards for Public Libraries in the Philippines, and ; 6) to know the strengths and weaknesses of the library collection and services.
This study follows the descriptive survey research method. The subjects are composed of the library users, the head librarian, and the library personnel of the Rizal Provincial Library. An estimate of 150 population serves as the library users. The ideal sample size of the population is 108. The Powell formula is applied to determine the size of the respondents.
The questionnaire that has served as a tool for gathering data given personally to the respondents. Document analysis is used to supplement other data. The collection of data is conducted during the second semester of school year 1995-1996.
Typescript.
Vita.
Thesis (Bachelor of Library Science)--University of the Philippines Diliman
Keywords: Public libraries--Library resources--Evaluation.; Rizal Provincial Library